College Sport Communicator Leaders’ Perceptions of Sport Information Operations - Kelly Elliott (Journal of Intercollegiate Sport)
Recent research indicates College Athletic Communicators (CACs) could benefit from more staff in the communication department (Elliott et al., 2023). However the request may not be supported by administration as additional staffing may not fit in the budget. Therefore, it appears imperative to evaluate no-cost options to alleviate the feelings of being under-appreciated and overworked. The College Sport Communicators (CSC)  professional association may be a strong advocate for the profession and may have the ability to provide needed resources for those serving in CAC positions. Therefore, the research presented in this study aims to explore the perspective and experiences of CSC leaders to evaluate how to better serve the CAC profession with an understanding of limited resources. In this study, semi-structed interviews with CSC leaders were conducted. Data provided by the participants indicate ways for CACs to avoid burn out and how athletic administrators can work to support the profession.